Immune mechanisms in epileptogenesis - Xu, Dan; Miller, Stephen D.; Koh, Sookyong (Frontiers in Cellular Neuroscience, 2013)
Epilepsy is a chronic brain disorder that affects 1% of the human population worldwide. Immune responses are implicated in seizure induction and the development of epilepsy. Pre-clinical and clinical evidence have accumulated to suggest a positive feedback cycle between brain inflammation and epileptogenesis. Prolonged or recurrent seizures and brain injuries lead to upregulation of proinflammatory cytokines and activated immune responses to further increase seizure susceptibility, promote neuronal excitability, and induce blood–brain barrier breakdown. This review focuses on the potential role of innate and adaptive immune responses in the pathogenesis of epilepsy. Both human studies and animal models that help delineate the contributions of brain inflammation in epileptogenesis will be discussed. We highlight the critical role of brain-resident immune mediators and emphasize the contribution of brain-infiltrating peripheral leukocytes. Additionally, we propose possible immune mechanisms that underlie epileptogenesis. Several proinflammatory pathways are discussed, including the interleukin-1 receptor/toll-like receptor signaling cascade, the pathways activated by damage-associated molecular patterns, and the cyclooxygenase-2/prostaglandin pathway. Finally, development of better therapies that target the key constituents and processes identified in these mechanisms are considered, for instance, engineering antagonizing agents that effectively block these pathways in an antigen-specific manner.